Interventions on informal healthcare providers to improve the delivery of healthcare services in low-and middle-income countries: a systematic review - Das, Saibal; Khare, Shweta; Eriksen, Jaran; Diwan, Vishal; Stålsby Lundborg, Cecilia; Skender, Kristina (Frontiers in Public Health, 2024)
Objective: Informal healthcare providers (IHCPs) play a big role in health systems in low-and middleincome countries (LMICs) and are often the first point of contact for healthcare in rural and underserved areas where formal healthcare infrastructure is insufficient or absent. This study was performed to systematically review the literature on various interventions ontargeting IHCPs in improving the delivery of healthcare services in LMICs.Methods: PubMed, Embase, and Cochrane CENTRAL databases were searched for studies that assessed any type of intervention among IHCPs to improve the delivery of healthcare services in any LMIC. Outcomes included changes in knowledge, attitude, and reported practice of appropriate case diagnosis and management; improved referral services; effective contraceptive use; and medication appropriateness (PROSPERO ID: CRD42024521739).